Association between pneumonia hospitalisation and long-term risk of cardiovascular disease in Chinese adults: a prospective cohort study. (January 2023) - Hu, Yizhen; Sun, Zhijia; Yu, Canqing; Guo, Yu; Pei, Pei; Yang, Ling; Chen, Yiping; Du, Huaidong; Sun, Dianjianyi; Pang, Yuanjie; Tian, Xiaocao; Gilbert, Simon; et al.
Summary: Background: Lower respiratory tract infections, including pneumonia, have been associated with short-term increased risk of cardiovascular disease (CVD). However, there is only limited evidence about the long-term impact of pneumonia on the cardiovascular system beyond one year. Methods: We conducted a prospective matched cohort study based on data from the China Kadoorie Biobank study of 482, 017 adults who were enrolled between June 25, 2004, and July 15, 2008, and were free of CVD at baseline and before pneumonia hospitalization. A total of 24, 060 patients hospitalised with pneumonia were identified until December 31, 2018, and were matched on age, sex, urban or rural areas, and decile of the frailty index to 223, 875 controls. We used the piecewise Cox proportional hazards model to estimate the hazard ratios (HRs) and their 95% confidence intervals (CIs) for pre-specified incident CVD outcomes, including ischaemic heart disease (IHD), arrhythmia, heart failure (HF), ischaemic stroke (IS), and hemorrhagic stroke (HS), at various time intervals through 10 years after pneumonia hospitalization. Findings: Of the 247, 935 pneumonia cases and controls included, the mean age (standard deviation) was 53.5 (10.4), and 40.8% (101, 159) were men. During follow-up, 2389 (9.9%) pneumonia cases developed IHD, 489 (2.0%) cases developed arrhythmia, 545 (2.3%) cases developed HF, 1764 (7.3%) cases developed IS, and 348 (1.4%) cases developed HS. After adjustment for sociodemographic characteristics, lifestyle factors, health status and medication, underlying conditions, and family history of CVD, the elevated CVD risk was highest within the first 30 days after pneumonia hospitalisation, with subsequent risk reductions varying by subtypes. The elevated risk remained until the eighth year after pneumonia hospitalisation for IHD, arrhythmia, and HF, with HRs (95% CIs) of 1.48 (1.13–1.93), 2.69 (1.70–4.25), and 4.36 (2.86–6.64), respectively. The risk of stroke associated with pneumonia hospitalisation remained elevated until the seventh year for IS (HR = 1.30; 95% CI: 1.04–1.63), and until the second year for HS (1.39; 1.07–1.80). The above associations were consistently observed across various characteristics of the participants. Interpretation: In middle-aged and older Chinese adults, pneumonia hospitalisation was associated with short- and long-term CVD risk, with the elevated risk of certain CVD outcomes persisting for up to 8 years. Funding: National Natural Science Foundation of China, the National Key R&D Program of China, the Chinese Ministry of Science and Technology, the Kadoorie Charitable Foundation in Hong Kong, the UK Wellcome Trust .